THE EFFECT OF ORAL RAMBUTAN HONEY ON ALKALINE PHOSPHATASE ACTIVITY IN DENTAL SOCKET WOUNDS HEALING PROCESS (IN VIVO) - Zahra Khairunnisa; Euis Reni Yuslianti; Henri Hartman (Journal of Health and Dental Sciences, 2026)
Tooth extraction is a procedure that causes injury to the dental socket, requiring a proper healing process. Rambutan honey contains flavonoids and calcium, which have been reported to accelerate wound healing by increasing alkaline phosphatase (ALP) activity in blood serum. This study aimed to analyze the effect of oral rambutan honey on ALP activity during dental socket wound healing. This laboratory experimental study involved 20 rabbits that underwent lower right incisor extraction. The subjects were divided into five groups: negative control, positive control, and three treatment groups. The positive control group received 255 mg of calcium, while the treatment groups were administered rambutan honey at doses of 0.7 mL (treatment 1), 1.4 mL (treatment 2), and 2.1 mL (treatment 3). Observations were conducted on days 0, 7, 14, and 40 to assess ALP activity levels. Data analysis was performed using ANOVA followed by the Post Hoc Tukey test, while the Kruskal-Wallis test was followed by the Mann-Whitney test. The results showed that oral administration of rambutan honey significantly increased ALP activity on days 7, 14, and 40 (p < 0.05). Among the tested doses, 0.7 mL was the most effective, as it promoted a rise in ALP activity within normal physiological limits. Oral rambutan honey has a significant impact on enhancing ALP activity during dental socket wound healing, suggesting its potential as a natural therapeutic agent for post-extraction recovery. DOI : 10.54052/jhds.v5n3.p243-252